Synthesis and Characterization of Barium Tetrafluoridobromate(III) Ba(BrF4)2. Issue 36 (26th November 2014) - Ivlev, Sergey; Sobolev, Vasily; Hoelzel, Markus; Karttunen, Antti J.; Müller, Thomas; Gerin, Ivan; Ostvald, Roman; Kraus, Florian
Abstract: Alkali and alkaline earth metal tetrafluoridobromates M I BrF4, M II (BrF4 )2 (M I = Na–Cs, M II = Sr, Ba) can be synthesized from the respective fluorides and BrF3 . The reaction of BaF2 with liquid BrF3 under Freon‐113 leads to the formation of Ba(BrF4 )2 as a colorless microcrystalline powder. Here, we discuss its formation kinetics and thermodynamics. The compound crystallizes in the tetragonal space group I 4 with a = 9.65081(11) Å, c = 8.03453(13) Å, V = 748.32(2) Å 3, and Z = 4 at 27 °C, and it is isotypic to Ba(AuF4 )2 . The structure contains square planar BrF4 – anions. The compound is stable at ambient conditions excluding moisture and at temperatures up to approximately 200 °C. Solid‐state computational calculations of the Raman and IR spectra are in good agreement with the experimentally obtained ones, and in combination with its powder X‐ray diffraction pattern, density measurement, thermodynamics, elemental and EDXRF analyses, this shows that the compound is pure. Abstract : The synthesis of Ba(BrF4 )2 and its characterization by various methods is presented. Tetrafluoridobromates(III) may be promising materials for the dry‐chemical recycling of solid noble‐metal wastes.